HLA-DRB1*03 is associated with systemic lupus erythematosus and anti -SSB production in South Tunisia - Hachicha, Hend; Kammoun, Arwa; Mahfoudh, Nadia; Marzouk, Sameh; Fourati, Hajer; Haddouk, Samy; Fakhfakh, Raouia; Feki, Sawsan; Frikha, Faten; Gaddour, Lilia; Hakim, Feiza; Bahloul, Zouheir; et al. (International Journal of Health Sciences, 2018)
Systemic Lupus erythematosus (SLE) is an autoimmune disease with various presentations. This variation is due to the interaction of hormonal, environmental and genetic factors. Associations between human leucocyte antigens and SLE have long been recognized in different ethnic populations and have been suggested to represent the most important association. Objectives: The objectives of this paper were to determine susceptibility and protection HLA class II markers for SLE and to highlight, for the first time, associations between HLA alleles and clinical and serological features in South Tunisia. Methods: We conducted a case-control study on 75 SLE patients and 123 healthy controls. The HLA class II DRB1/DQB1 of all patients and controls was genotyped using PCR-SSP technique. Statistical analysis was performed using SPSS software. Results: HLA-DRB1*03 was the principal classII allele associated with the genetic susceptibility to SLE (pc=0.02; OR=2.57; CI=(1.39-4.75); this allele was also associated with anti-SSB production (p=0.016; OR=4.00; CI=(1.24-12.96)). HLA- DRB1*01 was significantly more expressed in SLE patients with neurologic disorders (p=0.013; OR=20.25; CI= (1.87-219.21)). No allele was found to be protective against SLE in our study group. Conclusion: Our results show that in south Tunisia SLE is associated with HLA-DRB1*03 and that some clinical features of SLE may be inﬂuenced by speciﬁc DRB1 and DQB1 alleles.